2007
DOI: 10.1074/jbc.m700317200
|View full text |Cite
|
Sign up to set email alerts
|

O-Fucosylation Is Required for ADAMTS13 Secretion

Abstract: ADAMTS13 is a plasma metalloproteinase that cleaves von Willebrand factor to smaller, less thrombogenic forms. Deficiency of ADAMTS13 activity in plasma leads to thrombotic thrombocytopenic purpura. ADAMTS13 contains eight thrombospondin type 1 repeats (TSR), seven of which contain a consensus sequence for the direct addition of fucose to the hydroxyl group of serine or threonine. Mass spectral analysis of tryptic peptides derived from human ADAMTS13 indicate that at least six of the TSRs are modified with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 51 publications
4
126
0
Order By: Relevance
“…In particular, the O-fucosylation occurring at 6 TSP1 repeats of ADAMTS13 and the N-glycosylation process appear to be critical for folding, secretion and proteolytic activity of ADAMTS-13 (45). The protein folding machinery of the ER consists of three major classes of proteins: (i) foldases, (ii) molecular chaperones, and (iii) the oligosaccharide processing enzymes as well as lectin chaperones calnexin and calreticulin, which all are involved in protein quality control (46). Among the foldases, the peptidyl-prolyl…”
Section: Page 14 Of 30 Thrombosis and Haemostasismentioning
confidence: 99%
“…In particular, the O-fucosylation occurring at 6 TSP1 repeats of ADAMTS13 and the N-glycosylation process appear to be critical for folding, secretion and proteolytic activity of ADAMTS-13 (45). The protein folding machinery of the ER consists of three major classes of proteins: (i) foldases, (ii) molecular chaperones, and (iii) the oligosaccharide processing enzymes as well as lectin chaperones calnexin and calreticulin, which all are involved in protein quality control (46). Among the foldases, the peptidyl-prolyl…”
Section: Page 14 Of 30 Thrombosis and Haemostasismentioning
confidence: 99%
“…Since N-glycosylation can affect protein folding and secretion efficiency [e.g., synaptotagmin 1 and inhibin/activin (Han et al 2004;Antenos et al 2007)], it is possible that these sites in Stl either facilitate secretion in the absence of a strong signal peptide (Stl-B) or boost a weak signal sequence (Stl-A). Other ADAMTS oligosaccharide modifications, C-mannosylation and O-fucosylation, typically occur within the TSRs and can be important for function (e.g., ADAMTS13) (Gonzalez De Peredo et al 2002;Paakkonen et al 2006;Ricketts et al 2007). Capacity for C-mannosylation is noteworthy in the context of Stl, because the solitary central TSR of Stl (with no C-terminal TSRs) is one of the major structural differences that marginalize Stl within the ADAMTS family and because C-mannosylation occurs only on secreted proteins.…”
Section: Discussionmentioning
confidence: 99%
“…O-fucosylation occurs within the CSX(S/T)C sequence of TSRs, where the underlined Ser or Thr is fucosylated. This is a post-translational modification that requires that the module be folded and is mediated by O-fucosyltransferase 2 [22]. Studies of ADAMTS13 and ADAMTS-like-1/Punctin-1 have demonstrated that O-fucosylation of TSRs is critical for protein maturation and secretion [22,23].…”
Section: Carbohydrate Modificationsmentioning
confidence: 99%
“…This is a post-translational modification that requires that the module be folded and is mediated by O-fucosyltransferase 2 [22]. Studies of ADAMTS13 and ADAMTS-like-1/Punctin-1 have demonstrated that O-fucosylation of TSRs is critical for protein maturation and secretion [22,23]. Interestingly, this modification is so far unique for TSRs and is, for instance, distinct from O-fucosylation of EGF-like repeats, which is catalyzed by O-fucosyltransferase 1 [22,23].…”
Section: Carbohydrate Modificationsmentioning
confidence: 99%
See 1 more Smart Citation